Reversible Brain Death: A Rare Manifestation of Snake Envenomation - Ankusha Patra; Vrinda Goel; Shiva Narang; Amitesh Aggarwal (Indian Journal of Medical Specialities)
Snakebite is a serious public health problem and one of the priorities in WHO's list of neglected tropical diseases. It significantly increases morbidity and mortality associated with envenomation in India. A neurotoxic snakebite can present in the form of symptoms ranging from asymptomatic presentation, ptosis, and complete external and internal ophthalmoplegia to complete respiratory failure. This is a case report of a 22-year-old male, who presented with bilateral ptosis and impending respiratory failure. He soon became deeply comatose, with absent brain stem reflexes (mute plantar, fixed pupils, and the absence of the doll's eye reflex) which were suggestive of brain death. He was treated with polyvalent anti-snake venom, anticholinesterases, and supportive therapy and recovered completely with an excellent outcome.